Réponses

2013-12-20T17:25:24+01:00
A:(y+3) (y-3) = y²-9
 
B.(2x-1) : il manque la suite


C.(v-8) (v-2) = v²-10v+16

 
D.(3x-7) (2x-5) = 6x²-29x+35
2013-12-20T17:36:02+01:00
A.(y+3) (y-3) = y²-3²=y²-9 (identité remarquable sous la forme (a²-b²) = (a-b) (a+b) )
B.(2x-1) =
(2x-1) (2x+1) = 2x+1
(4x²-1) - 2x -1 =0
4x²-2x -2 =0
2 (2x²-x-1)=0  qui admet pour solution x=1
C.(v-8) (v-2)  = v²- 2v - 8v +16 = v²-10v +4² = v² - 8v + 4² - 2v = (v-4)² - 2v  (identité remarquable sous la forme (a-b)² = a² - 2ab +b²)
 D.(3x-7) (2x-5) = 6x² -15x -14x +35 = 6x²-29x + 35